2020
DOI: 10.1002/jcad.12350
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Implicit Racial Bias and Mindfulness in Mental Health Practitioners

Abstract: The mental health research literature on implicit bias is limited (Boysen, 2009), and little is known about how factors that are associated with self‐perceived multicultural counseling awareness, such as mindfulness, relate to implicit racial bias in practicing mental health professionals. Using a correlational research design, we examined the association between mental health practitioners' implicit bias, self‐perceived multicultural counseling competence, facets of dispositional mindfulness, and mindfulness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Our neural and behavioral findings pointed to stereotyping toward black men and white women. These results add to previous literature indicating that stereotyping and biases do exist within the counseling field (Abreu, 1999;Boysen & Vogel, 2008;Ivers et al, 2021). Counseling students, counselor educators, and practitioners must pay attention to assumptions they may unknowingly make toward members of these specific groups.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our neural and behavioral findings pointed to stereotyping toward black men and white women. These results add to previous literature indicating that stereotyping and biases do exist within the counseling field (Abreu, 1999;Boysen & Vogel, 2008;Ivers et al, 2021). Counseling students, counselor educators, and practitioners must pay attention to assumptions they may unknowingly make toward members of these specific groups.…”
Section: Discussionsupporting
confidence: 70%
“…Counselors and counselors-in-training have been found to have implicit biases as measured through IATs (Boysen & Vogel, 2008;Castillo et al, 2007;Ivers et al, 2021). Implicit biases and stereotyping may negatively affect the work of counselors in important ways.…”
Section: Stereotyping and Biases In Counselingmentioning
confidence: 99%
“…(3) currently in counseling for trauma; and (4) attending at least four individual counseling sessions with the same mental health professional. Including various categories of mental health services providers is common when investigating TA (Flückiger et al, 2018) and attitudes and behaviors displayed by the provider in counseling sessions (Ivers et al 2020). The final sample consists of 251 participants after removing 444 of them due to not meeting all four inclusion criteria (n = 397, 57.12%), the completion time cut-off score (n = 1, 0.14%) and attention checks cut-off score (n = 26, 3.74%), and for missing data (n = 20, 2.87%).…”
Section: Methods Participantsmentioning
confidence: 99%
“…Campbell et al (2018) expanded upon Ivers et al's (2016) work and found a positive relationship between dispositional mindfulness and MCC Knowledge, Awareness, Skills, and Relationship as well as a positive association between the duration of mindfulness practices and overall MCC. Ivers et al (2021) found that MHPs who more frequently engaged in mindfulness practices each week had lower scores of implicit racial bias favoring White individuals over Black, Asian, or Hispanic individuals. Lenes et al (2020) indicated that participants in color-conscious multicultural mindfulness training had increased MC knowledge and skills, increased awareness of privilege, and decreased blatant racism and institutional discrimination.…”
Section: Mindfulness and MCCmentioning
confidence: 92%
“…Ivers et al. (2021) found that MHPs who more frequently engaged in mindfulness practices each week had lower scores of implicit racial bias favoring White individuals over Black, Asian, or Hispanic individuals. Lenes et al.…”
Section: MCCmentioning
confidence: 99%